Drowsy Driving Among Nurses: Potential Impetus to Support Napping. (December 2022) - Westley, Jlynn A.; Peterson, Jessica; Cook, Bianca
Background: As shift workers, nurses are at an increased risk of drowsy driving because of long hours at work and/or short sleep periods between shifts. Methods: In this study, a descriptive cross-sectional cohort design was used to examine the prevalence of drowsy driving among nurses. Findings: An electronic survey was sent to 7, 217 nurses of which 2, 205 (30.5%) completed the survey. Thirty percent (672 nurses) reported having dozed off while driving during their commute to work. In addition, 44.6% (976) of nurses disclosed feeling unsafe or uncomfortable during their commute due to drowsiness or fatigue. Conclusion/Application to Practice: As shift workers, nurses are subject to drowsy driving and its untoward effects. Healthcare leaders and nurse executives are in a position to evaluate and explore fatigue mitigation strategies such as napping, as this may prove to be beneficial in supporting nurse well-being and public safety.